The distribution and role of downed woody debris in nutrient retention and cycling during early stand establishment - Wiebe, Scott (My University, 2013)
Coarse woody debris (CWD) in boreal ecosystems has been hypothesized to play an important nutritional role following stand-replacing disturbances such as fire or harvest. Sites with shallow soil over bedrock or those with coarse textured soils can be especially susceptible to overstory removal as low carbon and nutrient pools may limit stand productivity in subsequent rotations. This dissertation includes results from a series of in-situ and ex-situ experiments examining the nutritional role of CWD. The ex-situ experiment was designed to evaluate whether species (aspen, spruce), origin (fire, harvest), and/or decay class (1-5) influence the timing, and rate of nutrient release from CWD. Source/sink relationships of CWD leachate were largely a function of CWD decay stage for C (source, peaking at decay class 4 and then a slight decline in decay class 5), N (initial sink to eventual source) and P (initially a large source followed by low rate of release). Leachate values from harvested logs were similar to those of fire origin, with the exception of N and Mn, suggesting considerable volatilization of these two nutrients during wildfire events.
Keywords: Coarse woody debris (CWD); Boreal ecosystems; Dead wood; Forest productivity; Carbon storage; Biological diversity; Wood decay process